Egyptian-Turkish relations under President Sisi (2013-2019) - محمد اميرة اسماعيل (lark, 2019)
Summary: Egyptian-Turkish relations played an important and prominent role. They had a deep and deep relationship rooted in history and geography. The inevitability of geography in the eastern Mediterranean makes the relationship between the two countries an indispensable necessity, but these relations underwent a major transformation. Former President Hosni Mubarak in 2011, Turkey has become one of the largest supporters of Egypt in the region, which strengthened relations between the two countries, especially economic, and when President Mohamed Morsi was removed from office in 2013, Turkey’s course away from Egypt, Sisi power outlet J Egypt, Turkey quickly became one of the main opponents of Egypt.